How reliable and consistent is our learning community of inquiry? Psychometric qualities of the community inquiry survey instrument applied to a sample of higher education portuguese students - Moreira, J. António (2014)
The purpose of this study was to report on the adaptation and empirical evidence to support the validation of the Community of Inquiry Survey Instrument based on the Community of Inquiry (CoI) framework (Garrison, Anderson & Archer, 2000). The participants for this study were undergraduate students (n = 280) enrolled in blended online courses offered through Moodle platform during one semester at different Portuguese high schools and university, involving students of diverse courses (specially in Health and Education). Factor analysis of student responses identified a three factor model which was tested through confirmatory factor analysis and found to be an acceptable fit to the predicted population model. Results from this study suggest that the instrument is a valid, reliable, and nefficient measure of its dimensions; thereby the CoI survey holds promise as a useful evaluation tool for providing formative and summative feedback about the effectiveness of online courses and programs considering Garrison and collaborator’s model for constructing effective learning environments. The study also discuses potential implications of the CoI measures for innovations in the field of New Technologies in Education peculiarly in the nearest context of teaching and learning of emergent communities of practice, of learning and of inquiry web mediated.